2016
DOI: 10.4209/aaqr.2016.03.0130
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Effect of Springtime Biomass-Burning Aerosols over Northern Indochina during 7-SEAS/BASELInE 2013 Campaign

Abstract: The direct aerosol radiative effects of biomass-burning (BB) aerosols over northern Indochina were estimated by using aerosol properties (physical, chemical, and optical) along with the vertical profile measurements from ground-based measurements with integration of an optical and a radiative transfer model during the Seven South East Asian Studies/ Biomass-Burning Aerosols & Stratocumulus Environment: Lifecycles & Interactions Experiment (7-SEAS/BASELInE) conducted in spring 2013. Cluster analysis of backwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Over SEA, aerosols are mainly from urban and industrial emissions (organics, sulfate, nitrate, ammonium), black carbon from fossilfuel combustion and biofuel burning, volcanic ash, sea salts and dust transported by long distances, while during pre-monsoon extensive forest and vegetation fires occur (Chuersuwan et al, 2008;Hai and Kim Oanh, 2013;Tsai et al, 2013;Kanniah, 2014;Kanniah et al, 2016;Khan et al, 2016;Pani et al, 2018;Dahari et al, 2019). Therefore, aerosols are mixtures of various types creating hybrid particles and rendering their radiative effects highly uncertain (Pani et al, 2016). In addition, trace gases such as sulfur dioxide (SO 2 ), nitrogen oxides (NO x ), ammonia (NH 3 ) and carbon monoxide (CO) are precursors of inorganic (sulfate, nitrate, ammonium and their mixtures, NH 4 NO 3 , (NH 4 ) 2 SO 4 , NH 4 HSO 4 ) and organic aerosols after complex homogeneous or heterogeneous chemical reactions in the atmosphere (Pandolfi et al, 2012;Henschel et al, 2015;Kharol et al, 2018;EPA, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over SEA, aerosols are mainly from urban and industrial emissions (organics, sulfate, nitrate, ammonium), black carbon from fossilfuel combustion and biofuel burning, volcanic ash, sea salts and dust transported by long distances, while during pre-monsoon extensive forest and vegetation fires occur (Chuersuwan et al, 2008;Hai and Kim Oanh, 2013;Tsai et al, 2013;Kanniah, 2014;Kanniah et al, 2016;Khan et al, 2016;Pani et al, 2018;Dahari et al, 2019). Therefore, aerosols are mixtures of various types creating hybrid particles and rendering their radiative effects highly uncertain (Pani et al, 2016). In addition, trace gases such as sulfur dioxide (SO 2 ), nitrogen oxides (NO x ), ammonia (NH 3 ) and carbon monoxide (CO) are precursors of inorganic (sulfate, nitrate, ammonium and their mixtures, NH 4 NO 3 , (NH 4 ) 2 SO 4 , NH 4 HSO 4 ) and organic aerosols after complex homogeneous or heterogeneous chemical reactions in the atmosphere (Pandolfi et al, 2012;Henschel et al, 2015;Kharol et al, 2018;EPA, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the total amount of columnar aerosol is critical not only for studying its impact on human health but also on solar radiation, cloud condensation processes, and climate change over South and Southeast Asia (e.g. Dumka et al, 2015;Pani et al, 2016Pani et al, , 2018Singh et al, 2020). Since the high pollution levels is a major environmental and health issue in SEA countries, it is essential to understand the degree and the spatial extent of the decrease in air pollutants and aerosols due to restriction measures during the COVID-19 period in spring 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Extending from the optical closure modeling (Bell et al, 2013;Pani et al, 2016a) for regional biomass-burning aerosols, Pani et al (2016b) reported, for the first time, a detailed estimation of direct aerosol radiative effect (DARE) near source regions over northern SAP by using in-situ datasets (i.e., ground-based measurement of aerosol physical, chemical, and optical properties) and a radiative transfer model during the spring of 2013 BASELInE campaign. Their results provided strong evidence that biomass-burning aerosols (mainly water soluble and black carbon) enhance the surface cooling (as high as -33.5 W m -2 in 24-hour mean) as well as atmospheric warming (as high as +24.7 W m -2 ), which could significantly influence the diurnally-averaged radiative energetics.…”
Section: Remote Sensing Of Air Quality and Impact On Radiative Energementioning
confidence: 99%
“…The heating rates due to black carbon were higher than those due to the total aerosols. In a case study of two‐layer heavy smoke long‐range transport, enhanced aerosol radiative efficiency at both surface and lower atmosphere were found with high atmospheric heating rate of 1.3 K/day ( Pani et al, ).…”
Section: Introductionmentioning
confidence: 99%